Highly catalytic nanoenzyme of covalent organic framework loaded starch- surface-enhanced Raman scattering/absorption bi-mode peptide as biosensor for ultratrace determination of cadmium - Li, Jingjing; Shu, Yiyi; Li, Chongning; Jiang, Zhiliang (Frontiers in Nutrition, 2023)
High affinity peptides have been used in nanoanalysis, but there are no reports which combine peptides with a liquid crystal covalent organic framework supported soluble starch catalytic amplification system as a biosensor recognition element. In this study, a new, highly sensitive and selective bi-mode molecular biosensor has been developed for the determination of cadmium ion. Specifically, a highly catalytic and stable covalent organic framework supported soluble starch nanosol catalyst was fabricated such that a nanocatalytic indicator reaction system for HAuCl4-sodium formate was established based on surface-enhanced Raman scattering. The Au nanoparticles produced exhibited a surface plasmon resonance absorption peak at 535 nm and a surface-enhanced Raman scattering peak at 1615 cm-1. Combining the nanocatalytic amplification indicator system with the specific peptides reaction permitted a sensitive and selective surface-enhanced Raman scattering/absorption bi-mode platform to be developed for the determination of cadmium in rice. The linear range for surface-enhanced Raman scattering determination was 0.025–0.95 nmol/L and the detection limit was 0.012 nmol/L.